Answer:
4x+2
Step-by-step explanation:
(13x+x−53x)−(−43x+2)
Group all the same variables on each side.
(-39x)-(-43x+2)
-39x+43x+2
4x+2
Hope this helps :)
A because a colored circle means it’s greater than
By elimination:
y = 3x - 1
y = 2x + 2
Subtract the second equation from the first
0 = x - 1
y = 2x + 2
Subtract the first equation from the second
0 = x - 1
y = x + 3
Subtract the first equation from the second again
0 = x - 1
y = 4
Subtract x from both sides of the first equation
- x = - 1
y = 4
Divide the first equation by (-1)
x = 1
y = 4
<h3>
So, the solution is x = 1 and y = 4 {or: (1, 4)}</h3>
Answer:
In basicallity if a question such as this pops up, the correct way to go would first be to graph this. y=x-4 would be equivalent to x=4.
My paper work is below:
y = x - 4
0 = x - 4
-x = -4
x = 4
Hope this helped..